MAGNETIC PROPERTIES OF THE PEROVSKITE OXIDE PbV₁₋ₓ Feₓ O₃ INVESTIGATED BY ELECTRON PARAMAGNETIC RESONANCE SPECTROSCOPY - OKOS, A.; RAITA, Oana; POP, A. (Studia Universitatis Babeș-Bolyai Physica, 2017)
The perovskite oxide Pb(V1-xFex)O3 ( 0 ≤ x ≤ 0.75 ) was synthesised by solid state reaction under high pressure (HP) – high temperature (HT) conditions. The effect of partial substitution of V with Fe on magnetic properties of PbVO3 compound were studied by Electron Paramagnetic Resonance (EPR) spectroscopy measurements.